2017
DOI: 10.1016/j.bpj.2017.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Promotes Protein Binding by Affecting Membrane Electrostatics and Solvation Properties

Abstract: Binding of the retroviral structural protein Gag to the cellular plasma membrane is mediated by the protein's matrix (MA) domain. Prominent among MA-PM interactions is electrostatic attraction between the positively charged MA domain and the negatively charged plasma membrane inner leaflet. Previously, we reported that membrane association of HIV-1 Gag, as well as purified Rous sarcoma virus (RSV) MA and Gag, depends strongly on the presence of acidic lipids and is enhanced by cholesterol (Chol). The mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 62 publications
3
41
0
Order By: Relevance
“…budding but not HIV-1 Gag budding. Residues 18, 67, and 72 in ASV Gag have been implicated in PS binding in studies reported by Doktorova et al (21). The effects on targeting or budding of single (15) or triple substitutions were only partial (this report).…”
Section: Determinants Of Asv Gag Plasma Membrane Targetingsupporting
confidence: 51%
See 2 more Smart Citations
“…budding but not HIV-1 Gag budding. Residues 18, 67, and 72 in ASV Gag have been implicated in PS binding in studies reported by Doktorova et al (21). The effects on targeting or budding of single (15) or triple substitutions were only partial (this report).…”
Section: Determinants Of Asv Gag Plasma Membrane Targetingsupporting
confidence: 51%
“…This was especially found to be the case when the central MA region was removed. The ASV MA sequence in Gag is highly basic and binds phosphatidylserine-containing membranes through electrostatic interactions (21,(43)(44)(45). Such membrane interaction is blocked by RNA binding to this region (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the preparation of this manuscript, Doktorova et al (48) reported the X-ray structure of full-length ASV MA (155 amino acids) at 2.8 Å resolution. In this structure, residues 1-102 were resolved, but there was no interpretable electron density for residues 103-155, consistent with an unstructured conformation.…”
Section: Characterization Of Asv Matrix-membrane Interactionsmentioning
confidence: 99%
“…The increase in the polarity of the vesicle surface, which can be clearly observed in Figure S3 (blue and red symbols) in Supplemental material, is in agreement with a recently molecular dynamics calculated cholesterol-driven increase in membrane surface charge density. (Doktorova et al, 2017) On the other hand, the hydrophobic tail buried deep in the bilayer reduces the polarity of the middle bilayer as sensed by the doxyl nitroxide, green and brown symbols Figures 3b and 4b and Figure S4. The change in A + of 16-DSE is about two to three times larger than the change A + of TP, which is a strong indication that cholesterol is located below the polar shell deeper in the bilayer.…”
Section: Resultsmentioning
confidence: 99%